The detection and antimicrobial susceptibility profile of Shigella isolates from meat and swab samples at butchers' shops in Gondar town, Northwest Ethiopia - Legesse Garedew; Zenabu Hagos; Bidir Zegeye; Zelalem Addis (Elsevier, 2016)
Summary: Food borne pathogens are major causes of deaths, illnesses and billions of dollars of expenses. The burden of food borne illness is worsened by the ever increasing rate of antimicrobial resistance microbes. Shigella, a bacterial pathogen associated with food, is reported to account for higher prevalence rates of food borne illness in different settings. A cross-sectional study was conducted from February 10 to June 30, 2013, at the butcher houses of Gondar town in the Northwest of Ethiopia to assess the prevalence and antimicrobial susceptibility pattern of Shigella. Cattle raw meat and swab samples from selected critical control points, including knives, chopping boards, and the hands and noses of butchers, were collected and analyzed. The identification of Shigella was carried out using colony characteristics, the Gram reaction, and biochemical tests. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method. The overall hygienic status of the butcher shops was also assessed using a checklist. An observational analysis revealed that the sanitary condition of the butcher shops and their premises was poor. Of 306 samples screened, 10.5% were positive for Shigella. Approximately 7.4% of meat samples and 10.2% of swab samples were contaminated with Shigella. Out of the total Shigella isolates, 90.6%, 46.9%, 18.8% and 9.4% were resistant to ampicillin, amoxicillin, ceftriaxone and tetracycline, respectively. A multidrug resistance pattern was recorded in 27.8% of the isolates. In conclusion, the safety of meat sold at Gondar butchers houses was poor. The identified Shigella isolates showed high levels of drug resistance and multidrug resistance patterns for commonly used antimicrobials in veterinary and human medicine. Practicing wise use of antimicrobials and strict sanitary interventions at different critical control points is strongly recommended, in addition to further in-depth studies to prevent unprecedented consequences from shigellosis. Keywords: Shigella, Prevalence, Antimicrobial resistance, Butcher shops, Gondar town, Ethiopia